Multi-Risk Analysis of Geological Disasters In The Jailolo Coastal Area As A Disaster Mitigation-Based Tourism Development Strategy - Amelia, Risky; Pasongli, Hernita; Nelannya Latupeirissa, Asry; Saprudin, Saprudin; Aswan, Marwis (Mataram University, 2024)
The coast of Jailolo is a tourism area that has the potential of natural resources, namely the potential of village tourism. Developing village tourism potential greatly supports economic activities in increasing community income. The high potential for geological disasters has a negative impact on the Jailolo coastal area, especially village tourism destinations. The low level of community resilience to geological disasters is limited information and a need for more data on disaster risk in the Jailolo coastal area. Therefore, maximum efforts should be made to increase community knowledge related to tourism optimisation, reducing the impact and risk of geological disasters. For mitigation efforts to be maximally and well coordinated, a tourism development strategy is needed on the potential of village tourism on the coast of Jailolo based on disaster mitigation, including multi-risk mapping of geological disasters on the coast of Jailolo. The resulting multi-risk map can be used for safe planning and safe land use and reduces the risk of geological disasters in the Jailolo coastal tourism area. The method used was an exploratory and evaluative survey method with a quantitative approach. Primary data sources were collected by surveying vulnerable communities using questionnaires and interviews to obtain information on capacity. Data processing was carried out in the form of scoring and then mapped with the help of QuantumGIS software. The data analysis technique refers to the Regulation of BNPB No. 2 of 2012 on Disaster Risk Assessment. It uses the Multi Criteria Analysis method with the help of Geographic Information System (GIS) software. The results showed that the Jailolo coastal tourist destination has a high risk of earthquake and tsunami disasters (score 3, red colour). Earthquake and tsunami multi-risk mapping in the Jailolo coastal tourist destination area, West Halmahera, is one of the strategies for developing disaster mitigation-based tourist destinations. Keywords: coastal; tourism; multi-risk; geological disaster